REVIEW ARTIKEL: PENAPISAN FITOKIMIA DAN POTENSI AKTIVITAS BIOLOGIS TANAMAN BAJAKAH (Uncaria cordata (Lour.) Merr.) - Farhany, Farhany; Saleh, Chairul; Daniel, Daniel (PROSIDING SEMINAR KIMIA, 2024)
Bajakah (Uncaria cordata (Lour.) Merr.) is an endemic plant to Kalimantan which is widely used as medicine. Various studies have been conducted regarding the phytochemical content and biological activity of Bajakah. Phytochemical screening was carried out for the content of alkaloids, flavonoids, polyphenols, triterpenoids, steroids, saponins, and tannins. Literature studies show that Bajakah has antioxidant activity within ethanol fraction with a very strong capacity as indicated by an IC50 value of 49.22 ppm, within the nhexane fraction with a medium capacity as indicated by an IC50 value of 108.22 ppm, and within ethyl acetate fraction with a medium capacity as indicated by an IC50 value of 130.30 ppm. Bajakah is also known to have antihyperuricemia activity by reducing uric acid levels at extract doses of 5.3 mg/30gBW, 10.6 mg/30gBW, and 21.2 mg/30gBW. Anticholesterol activity was indicated by reducing cholesterol levels at extract doses of 5.3 mg/30grW (11.45%), 10.2 mg/30grW (12.89%), and 21.2 mg/30grW (21.05%). Antiinflammatory activity was showed by testing the ethyl acetate extract of Bajakah stem at doses of 200 and 400 mg/kgBW. The acute toxicity test showed an LD50 value of >5000 mg/kgBW; indicating that the butanol fraction of Bajakah is relatively harmless and has potential as a standardized herbal medicine (OHT). Keywords : Uncaria cordata (Lour.) Merr.), phytochemical screening, bioassay